2007
DOI: 10.1093/sleep/30.11.1577
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Architecture and NREM Alterations in Children and Adolescents with Asperger Syndrome

Abstract: This study shows peculiar CAP modifications in children with AS and represents an attempt to correlate the quantification of sleep EEG oscillations with the degree of mental ability/disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 36 publications
2
45
1
1
Order By: Relevance
“…Although we could not show any difference between children with ASD with and without learning difficulties, disturbed sleep patterns in ASD do appear to be different from those seen in children with intellectual disabilities 28 29. We speculate that such widespread and early effects on sleep duration reflect an underlying shared neuropathological basis between autism and disturbances of the biological clock 29 30.…”
Section: Discussioncontrasting
confidence: 67%
“…Although we could not show any difference between children with ASD with and without learning difficulties, disturbed sleep patterns in ASD do appear to be different from those seen in children with intellectual disabilities 28 29. We speculate that such widespread and early effects on sleep duration reflect an underlying shared neuropathological basis between autism and disturbances of the biological clock 29 30.…”
Section: Discussioncontrasting
confidence: 67%
“…Evidence has suggested that inadequate sleep in children with ASD tends to be associated with emotional/behavioral dysregulation (e.g., hyperactivity) rather than with daytime sleepiness [12]. However, not all previous studies supported this finding [4,5,15,49]. Further studies might want to examine differences in daytime sleepiness between children with ASD and typically developing children.…”
Section: Discussionmentioning
confidence: 93%
“…Sleep disturbances are the most frequent comorbid conditions for children with ASD [2]. Sleep disturbances are linked to a wide range of negative outcomes, including worsened autistic symptoms, impairments in cognitive and daily functioning in children with ASD [3][4][5][6], and elevated mental problems in their parents [7][8][9]. Furthermore, both cross-sectional [10] and longitudinal [11] evidence suggest that sleep disturbances in children with ASD can persist throughout childhood into later life.…”
Section: Introductionmentioning
confidence: 99%
“…[36,40] Microstructure alterations of REM sleep (immaturity in the organization of eye movements into discrete bursts, increased muscle twitches during REM sleep) are recurrent findings; conversely, NREM sleep microstructure alterations, disclosed by cyclic alternating pattern analysis, seem to be related to mental retardation and not to ASD itself. [36,41] The REM sleep microstructure alterations might reflect a serotoninergic and dopamine dysfunction of pontine tegmentum activity, causing a reduced ability to organize new information in a coherent system. [38,40,42,43] Moreover, the high percentage of undifferentiated sleep, the alterations in spindle activity (higher in children and lower in adults with autism), and the occurrence of epileptiform discharges during sleep are considered signs of immaturity of cortical activity and of cortical disinhibition.…”
Section: Sleep Polysomnographic Studiesmentioning
confidence: 99%